Minimizing N2O emissions and carbon footprint on a full-scale activated sludge sequencing batch reactor. (15th March 2015) - Rodriguez-Caballero, A.; Aymerich, I.; Marques, Ricardo; Poch, M.; Pijuan, M.
Abstract: A continuous, on-line quantification of the nitrous oxide (N2 O) emissions from a full-scale sequencing batch reactor (SBR) placed in a municipal wastewater treatment plant (WWTP) was performed in this study. In general, N2 O emissions from the biological wastewater treatment system were 97.1 ± 6.9 g N2 O–N/Kg NH 4 + − N consumed or 6.8% of the influent NH 4 + − N load. In the WWTP of this study, N2 O emissions accounted for over 60% of the total carbon footprint of the facility, on average. Different cycle configurations were implemented in the SBR aiming at reaching acceptable effluent values. Each cycle configuration consisted of sequences of aerated and non-aerated phases of different time length being controlled by the ammonium set-point fixed. Cycles with long aerated phases showed the largest N2 O emissions, with the consequent increase in carbon footprint. Cycle configurations with intermittent aeration (aerated phases up to 20–30 min followed by short anoxic phases) were proven to effectively reduce N2 O emissions, without compromising nitrification performance or increasing electricity consumption. This is the first study in which a successful operational strategy for N2 O mitigation is identified at full-scale. Graphical abstract: Highlights: N2 O emissions from a full-scale sequencing batch reactor were studied. N2 O accounted for 60% of the carbon footprint of the treatment plant. N2 O minimization was achieved implementing intermittent aeration at the bioreactor. Performance or electricity consumption were unaffected by N2 O minimization strategy.